Intracranial Complication of Rhinosinusitis from Actinomycosis of the Paranasal Sinuses: A Rare Case of Abducens Nerve Palsy - G. L. Fadda; M. Gisolo; E. Crosetti; A. Fulcheri; G. Succo (Case Reports in Otolaryngology)
Sinonasal actinomycosis should be suspected when a patient with chronic sinusitis does not respond to medical therapy or has a history of facial trauma, dental disease, cancer, immunodeficiency, long-term steroid therapy, diabetes, or malnutrition. Radiological evaluation with computed tomography and magnetic resonance imaging are important in differential diagnosis, evaluating the extent of disease, and understanding clinical symptoms. Endoscopic sinus surgery associated with long-term intravenous antibiotic therapy is the gold standard for treatment of sinonasal actinomycosis. We report an unusual case of abducens nerve palsy resulting from invasive sinonasal actinomycosis in a patient with an abnormally enlarged sphenoid sinus. A review of the current literature highlighting clinical presentation, radiological findings, and treatment of this uncommon complication is also presented.